The Impact of Group-based Ergonomic Exercise on Blood Pressure Among Individuals with Hypertension - Eka Roslita Boru Gultom; Ellia Ariesti; Berliany Venny Sipollo; Emy Sutiyarsih (Inspirasi Foundation, 2023)
Introduction: Hypertension is a disease in which a person's blood pressure exceeds normal limits, namely systolic pressure which is above 140 mmHg and diastolic which is above 90mmHg. Exercise that is suitable for people who suffer from hypertension is low impact exercise because it is an exercise with light movements and can be done by anyone, from children to adults, even to the elderly. One of the aerobic exercise for hypertension is ergonomic exercise. Objective: The purpose of this study was to determine The effect of ergonomic exercise on reducing blood pressure in hypertension sufferers. Method: The research design used is correlational quantitative with Wilcoxon Signed-Rank Test. The sampling technique used purposive sampling, with a total sample of 25 people. Result: Based on the results of the Wilcoxon Signed-Rank Test, it was obtained p = 0.000 where p <0.05, which means that there is an effect of ergonomic exercise on systolic and diastolic blood pressure in hypertension sufferers at Posyandu Brotojoyo, Tanjung Rejo Village, Sukun District, Working Area of the Janti Malang Health Center. Conclusion: Based on the results of the Wilcoxon Signed-Rank Test, p = 0.000, where p < 0.05, which means that there is an influence of ergonomic exercise on systolic and diastolic blood pressure in hypertension sufferers at Posyandu Brotojoyo, Tanjung Rejo Village, Sukun District, Janti Malang Health Center Working Area.